Management of COVID-19 infection in patients undergoing hemodialysis - Boushab Mohamed Boushab; Noukhoum Koné; Sidi El-Wafi Ould Baba; Mohamed Jeddou Ould Mohamed El Mokhtar Bellattv; Mohamed Moustava Ould Ahmed; Houssein Ould Habiboullah; El-Vak Ould Ahmed Baba; Oumar Ould Sidi Mohamed; Leonardo Kishi Basco (The Pan African Medical Journal, 2021)

(untitled)
Coronavirus disease 2019 (COVID-19), a pandemic affecting the world´s population, is particularly threatening to dialysis patients. The purpose of this study was to propose recommendations for prevention and containment of COVID-19 in hemodialysis center situated in a regional hospital in Mauritania. Both COVID-19-infected (n = 11) and -uninfected (n = 16) dialysis patients were hospitalized up to three weeks to improve patient management. All COVID-19-infected patients were cured. Patient care and hygiene in a safe environment are the key factors for a favorable outcome, even in resource-limited settings.